2016
DOI: 10.1111/eff.12287
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in spatial patterns of Oncorhynchus mykiss growth require year‐round monitoring

Abstract: Growth and movement of juvenile salmonids influence the expression of individual life history traits and production of adults at the population scale. We individually marked and recaptured juvenile Oncorhynchus mykiss over the course of a year in Murderers Creek, a semi-arid tributary to the South Fork John Day River in Northeast Oregon. We tagged O. mykiss in three reaches with differing stream gradient, stream temperature and fish density. Mean growth rates differed significantly among reaches and seasons wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(122 reference statements)
0
13
1
Order By: Relevance
“…While relative density was retained in the best model, with fish at higher densities growing more slowly than fish at lower densities, this effect was relatively minor over the range (5–1,652 parr per site) of population densities encountered. This contrasts with other studies that have revealed overwinter growth in juvenile salmonids as being strongly density‐dependent (Kaspersson & Höjesjö, 2009; Tattam, Li, Giannico, & Ruzycki, 2017; Teichert, Kvingedal, Forseth, Ugedal, & Finstad, 2010). Some studies have suggested that growth is density‐dependent when a salmonid population experiences exploitative competition, which occurs when resources are limited (Imre, Grant, & Cunjak, 2005, 2010).…”
Section: Discussioncontrasting
confidence: 81%
“…While relative density was retained in the best model, with fish at higher densities growing more slowly than fish at lower densities, this effect was relatively minor over the range (5–1,652 parr per site) of population densities encountered. This contrasts with other studies that have revealed overwinter growth in juvenile salmonids as being strongly density‐dependent (Kaspersson & Höjesjö, 2009; Tattam, Li, Giannico, & Ruzycki, 2017; Teichert, Kvingedal, Forseth, Ugedal, & Finstad, 2010). Some studies have suggested that growth is density‐dependent when a salmonid population experiences exploitative competition, which occurs when resources are limited (Imre, Grant, & Cunjak, 2005, 2010).…”
Section: Discussioncontrasting
confidence: 81%
“…This infrastructure provides information on movements of Pacific salmonids during the freshwater portions of their life history (Connolly et al 2008;Homel and Budy 2008;Zydlewski et al 2009). Within tributary streams, researchers have used PIT tags to document important seasonal components of movement, survival, and production of anadromous juvenile salmonids (Martens and Connolly 2014;Bennett et al 2016;Bouwes et al 2016;Tattam et al 2017). Passive integrated transponder tags are often used as a marking tool for estimating population abundance because of their potential to provide additional information upon resight or recapture (e.g., growth: Tattam et al 2017;production: Martens and Connolly 2014).…”
mentioning
confidence: 99%
“…Estimating population abundance in multiple seasons is vital to understanding survival bottlenecks for salmonids that exhibit a life history punctuated by large migrations (Bennett et al 2015;Tattam et al 2017). However, researchers need to be able to identify and avoid periods of migration when conducting MR surveys, as closed population mark-recapture models are not suited for estimating abundance of migrating populations (Kendall 1999;Temple and Pearsons 2007).…”
mentioning
confidence: 99%
“…In many systems, winter survival is hypothesized to be a limiting factor to freshwater population productivity [23] and reducing winter mortality is often an objective of largescale restoration efforts [24]. Though juvenile salmonids may be less active in winter and not achieve substantial growth in many cases, there is evidence that winter fish growth may exceed growth observed during other seasons for some fish [25]. Understanding winter habitat use and foraging ecology could help improve our ability to increase overwinter survival.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling during multiple seasons is more likely to capture any carry-over effects that span pre-pulse, pulse, and post-pulse. Food availability, along with temperature, strongly affect fish growth rates with extreme variation in growth between seasons [25,46]. Quantifying fish growth and food resources at multiple points in time are essential to avoid bias in assumptions and to identify ephemeral trophic pathways that could be disproportionately important during that season or in subsequent seasons.…”
Section: Discussionmentioning
confidence: 99%